Effect of different radiopacifying agents on the physicochemical properties of white portland cement and white mineral trioxide aggregate - Duarte, Marco Antonio Hungaro; Minotti, Paloma Gagliardi; Rodrigues, Clarissa Teles; Zapata, Ronald Ordinola; Bramante, Clovis Monteiro; Filho, Mário Tanomaru; Vivan, Rodrigo Ricci; Moraes, Ivaldo Gomes de; Bombarda de Andrade, Flaviana (Elsevier, 2012)
Introduction: The aim of this study was to evaluate the pH, calcium ion release, setting time, and solubility of white mineral trioxide aggregate (WMTA) and white Portland cement (WPC) combined with the following radiopacifying agents: bismuth oxide (BO), calcium tungstate (CT), and zirconium oxide (ZO). Methods: Fifty acrylic teeth with root-end filling material were immersed in ultrapure water for measurement of pH and calcium release (atomic absorption spectrophotometry) at 3, 24, 72, and 168 hours. For evaluation of setting time, each material was analyzed according to the American Society for Testing and Materials guidelines 266/08. The solubility test was performed according to American National Standards Institute/American Dental Association specification no. 57/2000. Solubility, setting time, and pH values were compared by using analysis of variance and Tukey test, and the values of calcium release were compared by the Kruskal-Wallis and Miller tests. The significance level was set at 5%. Results: The pH and calcium release were higher at 3 and 24 hours. WPC was the material with the higher values for both properties. WMTA had the greatest solubility among all materials (P <.05). All radiopacifiers increased the setting time of WPC, and WMTA had the shortest setting time among all materials (P < .05). Conclusions: All materials released calcium ions. Except for WPC/CT at 168 hours, all materials promoted an alkaline pH. On the basis of the obtained results, ZO and CT can be considered as potential radiopacifying agents to be used in combination with Portland cement. Copyright © 2012 American Association of Endodontists.
Keywords: MTA; physico-chemical properties; Portland cement; radiopacifying agents; alkali; aluminum derivative; bismuth; bismuth oxide; calcium; calcium derivative; calcium tungstate; contrast medium; mineral trioxide aggregate; oxide; silicate; tooth cement; tungsten derivative; water; zirconium; zirconium oxide; atomic absorption spectrometry; chemistry; comparative study; diffusion; drug combination; human; humidity; materials testing; pH; physical chemistry; solubility; temperature; time; Alkalies; Aluminum Compounds; Bismuth; Calcium; Calcium Compounds; Contrast Media; Dental Cements; Diffusion; Drug Combinations; Humans; Humidity; Hydrogen-Ion Concentration; Materials Testing; Oxides; Physicochemical Phenomena; Silicates; Solubility; Spectrophotometry, Atomic; Temperature; Time Factors; Tungsten Compounds; Water; Zirconium